Multi-stakeholder analysis of needs, perceptions, and sociocultural influences on multipurpose prevention technologies (MPT) in India - Suhas Shewale; Sampada Bangar; Nomita Chandhiok; Thilakavathi Subramanian; Mubashir Angolkar; Tumanlal Katendra; Seema Sahay (BMC, 2024)
Abstract Background To ensure the acceptability and effectiveness of potential Multipurpose Prevention Technologies (MPTs), understanding user needs, and preferences are crucial to inform the design of MPTs. This article aims to explore the perceptions towards potential MPT use and to explore the needs of multiple stakeholders in India within their social and behavioural contexts. Methods A qualitative multicentric study was conducted in three Indian states-Maharashtra, Karnataka, and Tamil Nadu. The study involved a total of 222 interviews: 77 in-depth interviews with women, including those from the general population, HIV-positive women, and street and brothel-based Female Sex Workers (FSWs); 84 in-depth interviews with men and 61 key informant interviews were conducted. Three focus group discussions were conducted with FSWs. Interviews explored perceptions of the potential MPTs, needs, and factors that may potentially affect their use and adherence. Interviews and FGDs were transcribed and translated verbatim. Thematic analysis approach was used to analyse the data in NVivo version 8. Result The following themes highlight the need and preferences among women for the potential MPT product: 1) Overall perceptions about new MPT, 2) People at high risk need long acting products, 3) Condom versus new MPT: potential of MPT, 4) Women empowerment through MPTs 5) Secrecy and confidentiality 6) Non-stigmatising MPT product positioning. Conclusion Several stakeholders in this study expressed their need for new MPTs, but concerns regarding confidentiality, privacy, stigma and, adherence were identified. Besides efficacy, characteristics such as the size, packaging, formulation, and texture of MPTs, should be taken into account when designing the MPT products, also considering the needs of women, specially, female sex workers.